Nasal Delivery of Asiatic Acid Ameliorates Scopolamine-Induced Memory Dysfunction in Mice - Su Lwin Lwin Myint; Ratchanee Rodsiri; Hattaya Benya-Aphikul; Tissana Rojanaratha; Garnpimol Ritthidej; Ridho Islamie (Hindawi Limited, 2024)
Asiatic acid (AA) has previously shown its neuroprotective effects, but low oral bioavailability limits its penetration into the brain. This study aimed to investigate the effect of intranasal AA administration in mice with memory dysfunction induced by scopolamine. Mice received either intranasal AA (INAA), oral AA (POAA3 or POAA30), or donepezil, followed by scopolamine for 10 days. Morris water maze (MWM) was performed on days 0-5, 30 min after treatment. Locomotor activity was conducted on day 6 followed by brain collection. In MWM, INAA treatment had significantly reduced escape latency on days 2-4, while POAA3 decreased escape latency on day 3 and POAA30 and donepezil decreased escape latency on day 4. INAA inhibited acetylcholinesterase activity, increased catalase protein expression, and decreased malondialdehyde levels in the brain tissue. Therefore, intranasal administration of AA produced a rapid onset in the protection of learning and memory deficits induced by scopolamine through acetylcholinesterase inhibition and antioxidant effect.